Psychoeducation: Healthy teens without porn - Islamiyati, Hikmah; Widuri, Erlina Listyanti (Universitas Muhammadiyah Magelang, 2021)
In the current era of globalization, the use of the internet is increasingly widespread, especially among teenagers. One of the characteristics of adolescent development is the existence of great curiosity, including in sexual matters that lead to access to pornography. The purpose of this activity is to provide community-based preventive interventions with psychoeducation. The results of the intervention were an increase in understanding about using the internet wisely, the impact of pornography addiction, knowledge about sex education and effective communication.